The effects of hospitalisation on children: A review - M. Bonn (AOSIS, 1994)
The aim of this article is to present a selective review of the research on children's psychological responses to hospitalisation. Children vary in their capacities to cope with the stress of hospitalisation. A significant proportion of them, however, suffer from some degree of emotional disturbance due to the experience. Prolonged and repeated hospitalisation increases the chance of later problems. The separation of the child from familiar figures during admission may be the cause of some of the emotional upset. Younger children, especially those between the ages of 6 months and 4 years are most vulnerable. Individual factors such as the children's temperament and intelligence contribute to their style of coping and thus may influence both the short term and long term effects of hospitalisation. Children who take an active coping role are more cooperative with hospital staff and show less disturbance after discharge. The preparation of children for the experience of hospitalisation has proven to be very effective in reducing their emotional distress during admission.